Association of cerebral microbleeds with cerebrospinal fluid Alzheimer‐biomarkers and clinical symptoms in early dementia with Lewy bodies. (26th December 2020) - Mendes, Aline; Noblet, Vincent; Mondino, Mary; Loureiro de Sousa, Paulo; Manji, Sumayya; Archenault, Anne; Casanovas, Michel; Bousiges, Olivier; Philippi, Nathalie; Baloglu, Seyyid; Rauch, Lucie; Cretin, Benjamin; et al.
Abstract: Objectives: To determine the prevalence, localization and associations of cerebral microbleeds (CMB) in dementia with Lewy bodies (DLB) with its core clinical symptoms and cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD). We hypothesize DLB patients with CMB have increased amyloid burden compared to those without CMB, which could also translate into clinical differences. Methods: Retrospective cross‐sectional analysis from the AlphaLewyMA study (https://clinicaltrials.gov/ct2/show/NCT01876459 ). Patients underwent a standardized protocol of brain MRI including 3D T1, 3D FLAIR and T2* sequences, and CSF analysis of AD biomarkers. CMB and white matter hyperintensities (WMHs) were visually assessed in prodromal and mild demented (DLB, N = 91) and AD (AD, N = 67) patients. Results: CMB prevalence did not differ among DLB and AD (24.2% vs. 37.3%; p = 0.081). CMB were mainly distributed in lobar topographies in both DLB (74%) and AD (89%). CMB in DLB was not associated with global cognitive performance, executive functioning, speed of information processing, or AD CSF biomarkers. Similarly, there was no difference regarding specific clinical symptoms: fluctuations, psychotic phenomena, sleep behavior disorder and Parkinsonism between DLB patients with and without CMB. AD patients with CMB had increased burden of WMH compared to those without (2.1 ± 0.86 vs. 1.4 ± 0.89; p = 0.005), according to Fazekas scale, whereas no significant difference was observed in DLB patients (1.68 ± 0.95 vs. 1.42 ± 0.91; p = 0.25). Conclusion: CMB were equally prevalent with similar topographic distribution in both DLB and AD patients. CMB was not associated with CSF AD biomarkers or core clinical symptoms in DLB.